Digitalization of information systems and educational laboratory management in higher education institutions - Fauzi, Rochmad; Ar Rosyid, Harits; Herwanto , Heru Wahyu (Bulletin of Social Informatics Theory and Application, 2024)
This study aims to develop an Information and Educational Laboratory Management System application based on SIONLAP. SIONLAP is designed and developed following educational institution elements' duties, needs, and functions. The system is developed to convert manual procedures, forms, and workflows into digital formats. Workflow processes can be optimized and automated through the implementation of SIONLAP. Documents and records generated by SIONLAP will be in digital data form, which can facilitate data processing and strategic analysis for planning, organizing, implementing, documenting, monitoring, reporting, evaluating, and developing educational laboratories, thereby improving management and continuous services in support of the implementation of the Tri Dharma of Higher Education. The research method refers to the waterfall method, with testing using the black box method. The results of the SIONLAP 2.0 application research show that it 1) provides more user-friendly user access management capabilities to facilitate users in higher education institutions with multi-role functions; 2) simplifies the data management and information workflow of equipment inventory; and 3) offers a laboratory asset rental feature as a means for higher education institutions to generate revenue from their laboratory assets